Tinjauan Hukum Islam Dalam Mengatur Marketing Fee Pada Kegiatan Promosi Pada Radio Di PT. Radio Start Srasi Swara 102.6 FM Panyabungan - Faisah, Nur (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2023)
Abstract: One way to improve your business is through promotional activities. Promotional activities can be carried out through radio media. Like PT. Radio Start Srasi Swara 102.6 FM Panyabungan offers promotional services to clients or vice versa clients who come to the radio office to enter into advertising contracts. Providing promotional services on radio in making payments must be done at the beginning of each month in accordance with applicable regulations, but in reality many clients pay at the end, in the middle or make payments in installments. Based on this problem, the author is interested in researching more deeply how marketing fees are paid for promotional activities at PT. Radio Start Srasi Swara 102.6 FM Panyabungan, and whether these promotional activities are in accordance with existing Islamic law reviews. The author uses a type of field research, namely conducting research directly at a location and looking for sources in the field. The technique that the author uses in collecting data is observation or direct observation regarding the process of the research object to be studied, then interviews conducted with the Directors, Marketing Team, Clients and collecting several related documents that can be used to help the research process and thesis preparation. The approach that the author takes in this research is a qualitative approach, namely the researcher will get results in the form of descriptive data in the form of people's speech, then the author describes it using the author's language so that it can be better understood by readers. After researchers have conducted research and analysis, it can be concluded that Marketing Fee Payments at PT. Radio Start Srasi Swara 102.6 Fm Panyabungan, carried out at the beginning of the month or according to the applicable contract and agreed upon by both parties. Advertising services on Radio Start Srasi Swara 102.6 Fm Panyabungan have fulfilled the first and second requirements, namely the person who entered into the contract and agreed to the contract, while for the third requirement, namely the salary, according to the researcher, it has not met the requirements because in reality the payment is late, violating the ijarah conditions that have been determined in Islamic law.